1980
DOI: 10.1037/0097-7403.6.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation rather than overshadowing in flavor-aversion learning: An analysis in terms of within-compound associations.

Abstract: Five experiments investigated the development of aversions to stimuli with strong odor components. Those odors were presented simultaneously with tastes are followed by lithium chloride. Contrary to expectations derived from previous investigations of compound conditioning, the presence of a taste stimulus at the time of conditioning was found to potentiate rather than overshadow the resulting odor aversions. Explanations in terms of either the taste's unconditioned aversiveness or nonassociative effects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
234
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(252 citation statements)
references
References 13 publications
13
234
5
Order By: Relevance
“…One important theoretical concept is that not only do the components of the compound form an association with the US, but they also form an association with each other (Rescorla and Cunningham 1978;Durlach and Rescorla 1980;Speers et al 1980;Holland and Ross 1981;Heth 1985). These withincompound associations were nicely demonstrated in an eloquent set of taste aversion experiments by Rescorla and Cunningham (1978) where rats were first exposed to two distinct flavors (hydrochloric acid and sucrose) presented in compound.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One important theoretical concept is that not only do the components of the compound form an association with the US, but they also form an association with each other (Rescorla and Cunningham 1978;Durlach and Rescorla 1980;Speers et al 1980;Holland and Ross 1981;Heth 1985). These withincompound associations were nicely demonstrated in an eloquent set of taste aversion experiments by Rescorla and Cunningham (1978) where rats were first exposed to two distinct flavors (hydrochloric acid and sucrose) presented in compound.…”
Section: Discussionmentioning
confidence: 95%
“…The purpose of this set of experiments was not to confirm or propose a specific configural or elemental theory based on previous research on combination laws and compound learning theories (Rescorla and Wagner 1972;Weiss 1972;Kamin and Gaioni 1974;Mackintosh 1976;Rescorla and Cunningham 1978;Durlach and Rescorla 1980;Kehoe and Gormezano 1980;Pearce and Hall 1980;Wagner and Brandon 2001), but rather to find a behavioral paradigm that could reduce fear expression to compound stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The first mechanism may have as its basis any model of associative learning which restricts the strength of the association between a target CS and a US when the target is conditioned in compound with another CS (e.g., Mackintosh, 1975;Pearce & Hall, 1980;Rescorla & Wagner, 1972). The second mechanism may have as its basis a model which explains potentiation in terms of the formation of within-compound associations (e.g., Durlach & Rescorla, 1980). According to this idea, pairing a compound of AB with a US results in the formation of associations between these stimuli and the US, plus reciprocal associations between A and B.…”
Section: Discussion -Experiments 1 Andmentioning
confidence: 99%
“…Furthermore, studies of flavor-aversion learning imply that the within-compound association analysis of potentiation may be incomplete. Durlach and Rescorla (1980) showed that the aversion to an odor that is normally potentiated by pairing an odor/taste compound with illness can be weakened by extinction of the taste CS. However, the same studies did not show that when the taste was nonreinforced, an underlying overshadowing effect was revealed-only that potentiation was abolished.…”
Section: Discussion -Experiments 1 Andmentioning
confidence: 99%
“…Recall that in the potentiation experiments described above, a low salience stimulus X is presented together with a more salient stimulus A and followed by O (usually after a trace). Because both X and A were presented simultaneously, an association between them is formed (the withincompound association; Durlach & Rescorla, 1980). Because X is of low salience, it becomes weakly associated with O.…”
Section: Competition and Facilitation 20mentioning
confidence: 99%